2020
DOI: 10.1108/aeds-05-2020-0119
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and challenges of online higher education in the era of COVID-19: a study of students' perspective

Abstract: PurposeEmergence of coronavirus disease 2019 (COVID-19) forced the world-wide education system to adopt online mode immediately. There are two main objectives of the paper: the first one is to know the acceptability of online mode of examination and learning amongst students by analysing the various aspects like difficulty, mental pressure, study pattern, etc. and the second one is to know the role of gender in adopting online education.Design/methodology/approachAn online survey is conducted amongst the stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
84
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 20 publications
12
84
1
3
Order By: Relevance
“…The study was performed using a survey for the first phase. The survey was developed based on the published literature, [6][7][8]18,19,21,22 and the SWOC analysis (Strengths, Weaknesses, Opportunities, and Challenges), that was carried out by the College of Pharmacy at the beginning of the academic year for routine planning and improvement. Two versions of the survey were developed; one for academic staff and another one for students.…”
Section: Development Of the Study Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was performed using a survey for the first phase. The survey was developed based on the published literature, [6][7][8]18,19,21,22 and the SWOC analysis (Strengths, Weaknesses, Opportunities, and Challenges), that was carried out by the College of Pharmacy at the beginning of the academic year for routine planning and improvement. Two versions of the survey were developed; one for academic staff and another one for students.…”
Section: Development Of the Study Toolsmentioning
confidence: 99%
“…However, the capacity for e-learning, underequipped pharmacy schools, and internet access service were major challenges. 7,21,22 Other examples include activation of the asynchronous teaching for pharmacy education shortly to cope and expand learning accessibility; remote delivery of the educational content due to subscriptions to various E-Systems, expert's readiness, the inclusion of active learning in the curriculum, and training instructors to use online platform for teaching such as (Zoom). 7,8,23 In the kingdom of Saudi Arabia, the Ministry of Education issued a notice, in March 2020, to suspend face-to-face teaching and learning and temporarily close all educational institutions because of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a previous study found that 67% percent of students had a positive experience with online exams (Matthíasdottir & Arnalds, 2016). However, Bisht, Jasola, and Bisht (2020) found that connecting to the internet is the most critical issue for students in online exams. Most online exams are only accessed if the user has an appropriate level of internet speed.…”
Section: Availability and Accessibilitymentioning
confidence: 99%
“…Curriculum delivery was found to be more common among male (β=0.19, t=2.26, p<0.05) students and high scorers (β=0.35, t=3.29, p<0.05), who believed that better suitability under the COVID-19 situation was due to better curriculum delivery. During the pandemic, with most of the education delivery being online, (Bisht et al, 2020) reported that Indian male students are discomforted with it. Recently, (Kundu & Bej, 2021) discovered in the Indian context that online learning during the pandemic is not suitable due to fear, insecurities, and a number of challenges associated with digital connections, (Wladis et al, 2014a) believed that online learning is concomitant with the risk of declining enrollments This might be the reason why curriculum delivery is crucial for male students during the pandemic.…”
Section: Curriculum Delivery Modementioning
confidence: 99%